El mercado chino como oportunidad de negocio y el crecimiento empresarial en la ciudad de Iquitos 2022 - Bardales Sánchez, Vanessa Indhyra (2022)
The objective of this study was to determine the relationship between the Chinese market as a business opportunity and business growth in the City of Iquitos 2022, since it was an applied research, descriptive - correlational level, experimental design, which was taken as a population and shows 50 entrepreneurs, the survey and questionnaire were used as a technique as an instrument to collect information, concluding that the Chinese market as a business opportunity is rated as regular (24%) since they report that taking advantage of the opportunity to import Chinese products today will sometimes bring you profits in the future, moreover, never hire staff with experience in importing and selling Chinese products; on the other hand, business growth is considered medium (26%) because business competitiveness sometimes generates the drive to achieve business success; Likewise, it reports that they sometimes make periodic estimates of the working capital that the company must have. Finally, a considerable positive relationship has been determined between the Chinese market as a business opportunity and business growth in the city of Iquitos 2022, corroborated by a Pearson correlation coefficient (0.766) with significance at the 0.000 level.